При , ! решение не нужно, только ответ.

инна103 инна103    3   22.07.2019 23:30    1

Ответы
KOTOMAKS06 KOTOMAKS06  19.08.2020 15:50
\frac{5x}{x^3-8}+\frac{10}{x-2}=\frac{5x}{(x-2)(x^2+2x+4)}+\frac{10}{x-2}=\\\\=\frac{5x}{(x-2)(x^2+2x+4)}+\frac{10(x^2+2x+4)}{(x-2)(x^2+2x+4)}=\\\\=\frac{5x+10(x^2+2x+4)}{(x-2)(x^2+2x+4)}=\frac{5x+10x^2+20x+40}{(x-2)(x^2+2x+4)}=\frac{10x^2+25x+40}{(x^3-8)}
Если х=4\frac{3}{5}=4,6, то выражение
\frac{10x^2+25x+40}{(x^3-8)}=\frac{10(4,6)^2+25*4,6+40}{((4,6)^3-8)}=\frac{211,6+115+40}{(97,336-8)}=\frac{366,6}{89,336}=\\\\=\frac{366600}{89336}=4\frac{9256}{89336}=4\frac{1157}{11167}
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра